2022
DOI: 10.14202/vetworld.2022.1924-1931
|View full text |Cite
|
Sign up to set email alerts
|

Risk-associated factors associated with the bovine viral diarrhea virus in dromedary camels, sheep, and goats in abattoir surveillance and semi-closed herd system

Abstract: Background and Aim: Bovine viral diarrhea virus (BVDV) is one of the most important viral pathogens causing high economic losses in cattle of all ages. Despite the active vaccination campaigns against BVDV, many outbreaks are still detected in various populations of cattle worldwide. Other species of animals such as dromedary camels, sheep, and goats may harbor BVDV infection and cause variable clinical syndromes. Thus, they may act as a source of infection to the cattle population around them. However, little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…We used the Kruskal-Wallis test to compare the prevalence of AEV among the tested locations as previously described [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Kruskal-Wallis test to compare the prevalence of AEV among the tested locations as previously described [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Blood specimens were obtained from the wing veins of domestic and wild birds as previously described [18][19][20]. Serum was obtained from the blood samples and stored at −20℃ for serologic testing.…”
Section: Sample Collection From Chickens and Wild Free-range Animalsmentioning
confidence: 99%
“…Similarly, a seroprevalence of 26% in Saudi Arabia and 35% in both Saudi Arabia and Oman was previously reported ( 27 30 ). Our previous serosurveillance of BVDV on non-bovine species of animals in the Eastern Region of Saudi Arabia showed seroprevalence of 4.5% in camels and 3.5% in goats, whereas none of the tested sheep sera were positive for anti-BVDV antibody, while AC-ELISA showed none of the tested samples was BVDV-positive ( 31 ).…”
Section: Introductionmentioning
confidence: 91%
“…In Egypt, BVD is prevalent among domestic ruminants such as sheep, goats, cattle, and buffaloes [22,23]; however, few studies have reported the BVDV infection in camels but in few governorates without assessment of risk factors for the infection.…”
Section: Introductionmentioning
confidence: 99%